Prešeren v Škrabčevem jezikoslovju - Toporišič, Jože (Slavistična revija, 2006)
Škrabec often mentioned Prešeren, i.e., there are twenty-seven such places. He most comprehensivley treated the last name of the Slovene national poet in its written and spoken forms.
Keywords: knjižni jezik; literary language; orthography; pravopis; Prešeren, France; priimki; Slovene langauge; slovenščina; surnames; Škrabec, Stanislav